2017
DOI: 10.3390/metabo7010007
|View full text |Cite
|
Sign up to set email alerts
|

QSRR Modeling for Metabolite Standards Analyzed by Two Different Chromatographic Columns Using Multiple Linear Regression

Abstract: Modified quantitative structure retention relationships (QSRRs) are proposed and applied to describe two retention data sets: A set of 94 metabolites studied by a hydrophilic interaction chromatography system under organic content gradient conditions and a set of tryptophan and its major metabolites analyzed by a reversed-phase chromatographic system under isocratic as well as pH and/or simultaneous pH and organic content gradient conditions. According to the proposed modification, an additional descriptor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Zisi et al. [43] performed QSRR for 94 metabolite standards and their results indicated that the inclusion of RTs from a different chromatographic column as an additional descriptor improves prediction accuracy.…”
Section: Retention Time Prediction In Lc–ms‐based Metabolomicsmentioning
confidence: 99%
“…Zisi et al. [43] performed QSRR for 94 metabolite standards and their results indicated that the inclusion of RTs from a different chromatographic column as an additional descriptor improves prediction accuracy.…”
Section: Retention Time Prediction In Lc–ms‐based Metabolomicsmentioning
confidence: 99%
“…[ 68 ]. The connection between the molecular descriptors and the retention time can be established by artificial neural network, machine learning algorithms [ 69 , 70 , 71 , 72 , 73 ] or by boosted trees regression (BRT) [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tropsha and Golbraikh 18 , the numerical model that represents the relation between the molecular descriptors and the retention time can be established by numerous machine learning algorithms, or by using the artificial neural network (ANN), which is used in this study as it has already been proven to be an excellent tool in published literature. 11,19 The aim of this paper was to establish a new QSRR model for predicting the retention times of chemical compounds in A. clypeolata essential oil obtained by hydrodistillation and analyzed by GC-MS using the genetic algorithm (GA) variable selection method and the artificial neural network (ANN) model.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%